The kingdom of speech - Wolfe, Tom (New York : Little, Brown and Company, 2016)
"Taking readers on a rollicking ride through history, a master storyteller and reporter, whose legend began in journalism, presents a paradigm-shifting argument that speech, not evolution, is responsible for humanity's complex societies and achievements"--NoveList.
"Before Tom Wolfe was a bestselling novelist, he was a groundbreaking journalist. Now the maestro storyteller turns his attention to the mystery behind the creation of his own most important tool: language. In The Kingdom of Speech, Wolfe makes the captivating, paradigm-shifting argument that speech--not evolution--is responsible for humanity's complex societies and achievements. From Alfred Russel Wallace, the self-taught Englishman who beat Charles Darwin to the theory of natural selection but later renounced it for its inability to explain human speech, to the neo-Darwinists, who for years argued that there is a language 'organ' in the human brain, Wolfe examines how science has repeatedly tried and failed to account for man's gift of gab. Flash forward to the present day and the controversial work of another outsider, anthropologist Daniel Everett. After thirty years of studying a tribe isolated deep in the jungles of the Amazon, Everett revealed a people whose prehistoric level of speech had led to a society without religion, ceremonies, hierarchies, marriage, or ornaments, and without the ability to plan ahead or to consider a past beyond personal lifetimes, thus defying the current wisdom that language is hardwired in humans. With trenchant wit and uproarious humor, Wolfe cracks open the secretive, solemn, long-faced, laugh-out-loud zigzags of Darwinism, both old and neo-, and he shows the endless importance of the courageous outsider in overturning our most cherished ideas about ourselves. Provocative and fast-paced, Wolfe's latest tour de force will have everyone talking."--Dust jacket.
The beast who talked -- Gentlemen and old pals -- The dark ages -- Noam Charisma -- What the flycatcher caught -- The firewall.
Includes bibliographical references (pages 170-185).
Keywords: Language and culture; Speech; Human evolution; Oral communication; Social history; Language and languages -- Origin; Historical linguistics